2014
DOI: 10.1021/sc500085m
|View full text |Cite
|
Sign up to set email alerts
|

Mo-Doped Cerium Gadolinium Oxide as Environmentally Sustainable Yellow Pigments

Abstract: Mo-doped Gd 1 Ce 1−x O 3.5+Y (where x ranged from 0 to 0.3) oxides were synthesized as inorganic yellow pigments, which are benign and sustainable. The pigments exhibited good yellow color, with the yellowness value using the CIELAB 1976 system being around 39. In comparison to the existing reports on benign yellow pigments, which have been synthesized using high temperature calcination routes, this pigment has been synthesized through a low temperature sol−gel calcination route. The process also provided for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…As observed, all spectra display a broad adsorption band starting at about 580 nm and centered at about 400 nm. Such an absorption in the blue region could be attributed to an O2p-Ce4f charge transfer transition, following a previous report on Modoped cerium oxide based pigments [6], and is responsible for the yellow color observed for the samples (Fig. 10, inset).…”
Section: Optical Propertiessupporting
confidence: 77%
See 1 more Smart Citation
“…As observed, all spectra display a broad adsorption band starting at about 580 nm and centered at about 400 nm. Such an absorption in the blue region could be attributed to an O2p-Ce4f charge transfer transition, following a previous report on Modoped cerium oxide based pigments [6], and is responsible for the yellow color observed for the samples (Fig. 10, inset).…”
Section: Optical Propertiessupporting
confidence: 77%
“…Consequently, the development of alternative pigments, which are environmentally benign, is being a research topic of high interest. In this context, several new yellow pigment have been proposed which include some rare earth (RE) based phases such as titanium doped cerium molybdate [4], titanium doped praseodymium molybdate [5], molybdenum doped cerium oxide [6] and sodium cerium mixed molybdate [7]. However, to the best of our knowledge, none of these materials has been synthesized in the form of uniform and well dispersed nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] It is important the systematic research of the rare earth hosted in different kind of crystals with good structural, morphology, and optical properties as an efficient emitting material. Rare earth (RE) phosphors with unique physic-chemical properties (magnetic, electrical, electronic, optical and so forth) makes them critically important in magnets, superconducting and electronic material, medical imaging and cancer therapy, pigments, phosphor screens and fluorescent materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this present work, Gd 2 (SO 4 were obtained by decomposing the gadolinium dodecyl sulphate complex in air atmosphere at 400 °C and 900 °C for 2 h, respectively. To the best of our knowledge, the investigation on growth mechanism of gadolinium oxysulfate from gadolinium dodecyl sulphate by the simple complexation-thermal decomposition (CTD) method has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a number of non-toxic inorganic pigments have been reported by several researchers in order to replace the toxic pigments with the environmentally-friendly or less-toxic ones. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In particular, development of novel red pigments has been required and several studies have been reported. [18][19][20][21][22][23][24][25][26][27] Among them, it has been reported that Ca 1Àx La x TaO 2Àx N 1+x and Ce 2 S 3 showed bright red colour.…”
Section: Introductionmentioning
confidence: 99%